COVID-19 pandemic: insights into molecular mechanisms leading to sex-based differences in patient outcomes. (3rd August 2021) - Kumar, Ashutosh; Narayan, Ravi K.; Kulandhasamy, Maheswari; Prasoon, Pranav; Kumari, Chiman; Kumar, Sujeet; Pareek, Vikas; Sesham, Kishore; Shekhawat, Prakash S.; Kant, Kamla; Kumar, Santosh
Abstract: Recent epidemiological studies analysing sex-disaggregated patient data of coronavirus disease 2019 (COVID-19) across the world revealed a distinct sex bias in the disease morbidity as well as the mortality – both being higher for the men. Similar antecedents have been known for the previous viral infections, including from coronaviruses, such as severe acute respiratory syndrome (SARS) and middle-east respiratory syndrome (MERS). A sound understanding of molecular mechanisms leading to the biological sex bias in the survival outcomes of the patients in relation to COVID-19 will act as an essential requisite for developing a sex-differentiated approach for therapeutic management of this disease. Recent studies which have explored molecular mechanism(s) behind sex-based differences in COVID-19 pathogenesis are scarce; however, existing evidence, for other respiratory viral infections, viz. SARS, MERS and influenza, provides important clues in this regard. In attempt to consolidate the available knowledge on this issue, we conducted a systematic review of the existing empirical knowledge and recent experimental studies following Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines. The qualitative analysis of the collected data unravelled multiple molecular mechanisms, such as evolutionary and genetic/epigenetic factors, sex-linkage of viral host cell entry receptor and immune response genes, sex hormone and gut microbiome-mediated immune-modulation, as the possible key reasons for the sex-based differences in patient outcomes in COVID-19.